2015
DOI: 10.1021/acs.organomet.5b00699
|View full text |Cite
|
Sign up to set email alerts
|

Borane-Bridged Ruthenium Complex Bearing a PNP Ligand: Synthesis and Structural Characterization

Abstract: Reaction of the precursor complex [RuHCl(CO)(PPh 3 ) 3 ] with the PNP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…The complexes containing similar bridging R–BH 3 ···Ru interactions have been reported to exhibit dynamic (B H 3 ···Ru signals at δ = +3 to −4 ppm) or static (bridging B– H ···Ru signals at δ = −6 to −14 ppm) behavior in the 1 H NMR spectra at room temperature. 19 Complex 7 is a rare example of a carborane cluster with an exohedral B–B bond to a simple borane, and it is the first example of the regioselective formation of such a bond under metal-promoted conditions. 20 This compound may also be considered as a snapshot of a probable intermediate in transition-metal-catalyzed synthesis of diboranes, which is an increasingly important area of organometallic research due to the rise to prominence of diborane reagents for borylation chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…The complexes containing similar bridging R–BH 3 ···Ru interactions have been reported to exhibit dynamic (B H 3 ···Ru signals at δ = +3 to −4 ppm) or static (bridging B– H ···Ru signals at δ = −6 to −14 ppm) behavior in the 1 H NMR spectra at room temperature. 19 Complex 7 is a rare example of a carborane cluster with an exohedral B–B bond to a simple borane, and it is the first example of the regioselective formation of such a bond under metal-promoted conditions. 20 This compound may also be considered as a snapshot of a probable intermediate in transition-metal-catalyzed synthesis of diboranes, which is an increasingly important area of organometallic research due to the rise to prominence of diborane reagents for borylation chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…30 Addition of NaBH 4 to 2 in THF resulted in a color change from yellow to orange and eventually green upon workup and extraction with Et 2 O. Crystallization yielded dark green prisms from concentrated Et 2 O/pentane solutions at −25 °C that revealed that the second nitrogen in 2 had indeed been deprotonated as desired, but the reaction unexpectedly led to the isolation of N-capped, borane-bridged hydride Ru[(μ-H)BH 2 ]( Me SNNS Me )(PPh 3 ) (5) (Figure 5). Langer, Gade, and Trincado and Gruẗzmacher separately reported this type of MLC BH 3 binding across tricoordinate N-centered ligands with Fe, 41 Ru, 42 and Rh, 43 respectively. MLC binding of BH 3 has also been observed across a Ru−thiolate bond involving a tetradentate S 2 N 2 ligand with an ethylenediamine backbone and thiolate groups instead of thioethers.…”
Section: ■ Introductionmentioning
confidence: 91%
“…A few reactions at the nitrogen atom of the central N ‐heterocycle, however, have been reported in addition to the N–N bond formation in CbzC ( i Pr PNP)‐coordinated zirconium complexes, which has been discussed above (Scheme ). The crystallographically characterized CbzC ( Ph PNP)‐ruthenium complex 92 , for example, was found to exhibit a four‐membered N‐B‐H‐Ru metallacycle (Scheme ) . This structural motif was also found in a manganese complex bearing the acridane‐based PNP ligand scaffold (cf.…”
Section: Pnp Pincers and Their Reactivity Patternsmentioning
confidence: 98%
“…Scheme ), this procedure has not found widespread use, although exceptions are known. For CbzC ( Ph PNP)H, for example, the NH‐containing ruthenium complex 5 has been isolated and in turn converted into the pincer derivative 6 via reaction with KO t Bu (see Scheme ) . Intermediates such as 5 may also play a role in cases, where bases are mixed with the ligand and the metal precursor at the same time (as in the synthesis of CbzC ( i PrPNP)Cu from CbzC ( i PrPNP)H, LiO t Bu and CuCl or Pyr ( i PrPNP)Ir(cod) from Pyr ( i PrPNP)H, [(cod)Ir( µ ‐Cl] 2 and KO t Bu).…”
Section: Preparation Of Pnp Pincer Complexesmentioning
confidence: 99%